EDITORIAL NOTE Vol. 58 (12/2023) RA’E GA – THE GEOGRAPHIC SPACE UNDER ANALYSIS - Breunig, Fábio Marcelo (Ra'e Ga: o Espaço Geográfico em Análise, 2023)
RA’E GA is pleased to present to the national and international scientific community the third volume of 2023 (V.58 – 12/2023 - DOI: http://dx.doi.org/10.5380/raega.v58i0), which encompasses articles covering various topics related to Geographic knowledge and other areas of scientific expertise. This edition of the Journal maintains the publication flow in English and Portuguese. This change aimed to preserve the Papers construction structure of the texts and increase access for different readers. On this time, RA'E GA, on behalf of the entire editorial board, reviewers, authors, and readers, publicly thanks Ph.D. Tony Vinícius Moreira Sampaio (UFPR), Editor-in-Chief of the Journal, who for many years dedicated himself to RA'E GA. Their contributions helped RA'E GA achieve the A1 extract of QUALIS-CAPES (2017-2020), with strong work to maintain the editions regularity, reduce the time for issuing the first position, publication in Portuguese and English and, mainly, seeking manuscripts with an increasing impact on the academic community. Thank you very much Tony! RA’E GA extends its gratitude to the authors, the editorial team, section editors, and reviewers, especially those who contributed to this volume (Adalto Lima, Izabela Mendes, Fátima Verônica Pereira Vila Nova, Agnes de Araujo, Sirius Souza, Maria Salvador, Tony Sampaio, Leila Limberger, Gabriela Goudard, Carina Petsch, Carlos Gamba, Gracieli Trentin, Eduardo Petrucci, Jakeline Baratto, Valdir Steinke, Fábio Marcelo Breunig), as well as the Program for Support of Periodical Scientific Publications at UFPR. All of these activities are crucial for the advancement of Brazilian scientific research and have been instrumental in ensuring the quality of this current volume.